Association of Noise Annoyance with Measured Renal Hemodynamic Changes - Kannenkeril, Dennis; Jung, Susanne; Ott, Christian; Striepe, Kristina; Kolwelter, Julie; Schmieder, Roland; Bosch, Agnes (Kidney & Blood Pressure Research, 2021)
Background: Chronic mental stress is recognized as a modifiable risk factor for cardiovascular disease. The aim of this study was to demonstrate that noise annoyance-induced stress is associated with changes in renal hemodynamics. Methods: Renal hemodynamic parameters were measured using steady-state input clearance with infusion of para-aminohippuric acid and inulin in individuals with normal, high normal, and elevated blood pressure. All individuals ranked subjective annoyance due to noise in everyday life on a 7-grade Likert scale. The median of all rankings was used as a cutoff point to divide the group into noise-annoyed and non-noise-annoyed individuals. Different renal hemodynamic parameters were calculated based on the Gomez equation. Results: Noise-annoyed individuals (n = 58) showed lower renal plasma flow (599 +/- 106 vs. 663 +/- 124 mL/min, p = 0.009), lower renal blood flow (1,068 +/- 203 vs. 1,172 +/- 225 mL/min, p = 0.047), higher filtration fraction (22.7 +/- 3.3 vs. 21.3 +/- 3.0, p = 0.012), higher renal vascular resistance (88.9 +/- 25.6 vs. 75.8 +/- 22.9 mm Hg/[mL/min], p = 0.002), and higher resistance of afferent arteriole (2,439.5 +/- 1,253.4 vs. 1,849.9 +/- 1,242.0 dyn s(-1) cm(-5), p = 0.001) compared to non-noise-annoyed individuals (n = 55). There was no difference in measured glomerular filtration rate (133 +/- 11.8 vs. 138 +/- 15 mL/min, p = 0.181), resistance of efferent arteriole (2,419.4 +/- 472.2 vs. 2,245.8 +/- 370.3 dyn s(-1) cm(-5), p = 0.060), and intraglomerular pressure (64.0 +/- 3.1 vs. 64.6 +/- 3.5 mm Hg, p = 0.298) between the groups. After adjusting for age, renal plasma flow, renal blood flow, and renal vascular resistance remained significantly different between the groups, with a trend in increased afferent arteriolar resistance and filtration fraction. Conclusion: In this study, noise annoyance was associated with reduced renal perfusion attributed to increased renal vascular resistance predominantly at the afferent site. Long-term consequences of this renal hemodynamic pattern due to noise annoyance need to be investigated.
CRIS-Team WoS Importer:2021-05-14